ANALISIS KEGIATAN PERDAGANGAN SAHAM DAN VARIABILITAS RETURN SAHAM DISEKITAR HARI PENGUMUMAN LAPORAN KEUANGAN TAHUNAN - Ismail Said (Akutansi Bisnis & Manajemen ( ABM ), 2001)
This study is aimed to analyzing whether the annual financial report announcement at the Jakarta Stock Exchange (JSX) has significant influence on the variables of stock trading activities and stock return variability. The research is conducted by the observation of highest-rank corporation stocks ranked by volume and trade value at the JSX, i.e. 21 samples of corporation stocks of 1996 and 24 samples of corporation stocks of 1997. The data needed were the total number of stock traded daily, the total number of stock traded distributed, the daily stock price (closing price), the composite stock price index, the Bank Indonesia Certificate interest, and the announcement date of the annual financial report of 1996 and 1997. The activity of stock trading perceived from the indicator of Trading Volume Activity (TVA). Meanwhile the stock return variability was seen through the indicator of Security Return Variability (SRV). The stock expected return was estimated using the Capital Asset Pricing Model (CAPM). The t-test (two-tailed test) was also used to test the hypothesis. Hypothesis testing with 5% level of significance revealed that the null hypothesis was accepted and the alternative hypothesis was refused. Therefore, it is concluded that no influence was evident of the annual financial statement announcement on the stock trading activity and the stock return variability at the JSX. In order words, the annual financial statement announcement at the JSX had no information content for the investor.